ANTECEDENTS AND IMPACTS OF STUDENTS’ ETHICAL PERCEPTION IN ACCOUNTING LEARNING PROCESS - Istiningrum, Andian Ari (UI Scholars Hub, 2014)
The objectives of this research are to get knowledge about what contributions that higher education can provide to build students’ ethical perception and awareness of fraud prevention. To achieve these objectives, the research was conducted toward accounting students at Yogyakarta State University. Data were collected using questionnaires distributed to 149 students. The analysis of the data used path analysis. Based on the result of the survey to the respondents, the research provides evidence that higher education has a positive and significant influence to build students’ ethical perception through internalizing objectivity and professional responsibility in the intermediate auditing course. In addition, it is also proven that accounting students who have high level of ethical perception are able to build awareness of fraud prevention.